An amine-modified honeycomb adsorption module and a method for manufacturing the same

CN118341400BActive Publication Date: 2026-10-27CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310060375.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2026-10-27
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

但目前现有技术制备的蜂窝活性炭主要用于挥发性有机化合物(VOC)等气体净化领域,比表面积小、且对CO2吸附效果较差,难以满足大规模碳捕集技术的应用需求

Benefits of technology

[0019]通过上述技术方案,本公开提供的制备方法通过采用低灰分煤和煤沥青为原料,然后经过预氧化、炭化及第一活化,得到高比表面积的活性炭材料,再通过添加粘结剂制备出高比表面积、孔道结构适宜的蜂窝吸附模块,对其进行有机胺浸渍处理,可以得到一种新型胺改性蜂窝吸附模块,该胺改性蜂窝吸附模块的CO2吸附量显著提高。本公开的制备方法工艺简单,无废液产生,适合大规模生产和应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004061142710000121
    Figure BDA0004061142710000121
Patent Text Reader

Abstract

The present disclosure relates to an amine-modified honeycomb adsorption module and a preparation method thereof, which comprises: (1) mixing low-ash coal and coal pitch, pre-oxidizing, carbonizing and first activating the obtained mixture to obtain activated carbon material; (2) mixing the activated carbon material, a binder, water and optional auxiliary agents, vacuuming the obtained mixture, shaping and second activating to obtain the honeycomb adsorption module; (3) immersing the honeycomb adsorption module in a solution containing an organic amine, and drying the obtained material; wherein the content of ash in the mixture is 5 wt% or less based on the total weight of the mixture. The preparation method of the present disclosure is simple, no waste liquid is generated, the CO2 adsorption capacity is significantly improved, and is suitable for large-scale production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of adsorbent preparation technology, specifically to an amine-modified honeycomb adsorption module and its preparation method. Background Technology

[0002] Adsorption carbon capture technology is widely recognized as a second-generation carbon capture technology due to its low energy consumption, significant potential for cost reduction, flexible operation, and environmental friendliness, and it has good application prospects and potential. However, adsorption carbon capture technology currently suffers from problems such as low adsorption material capacity, small flue gas flux, and large bed pressure drop, making it difficult to apply this technology on a large scale in the short term.

[0003] Honeycomb activated carbon, with its regular shape, ease of modification and processing, and high wear resistance, thermal conductivity, strength, low pressure drop, and fast adsorption-desorption rates, is a novel carbon material with excellent adsorption-desorption properties. However, currently available honeycomb activated carbon is mainly used for the purification of volatile organic compounds (VOCs) and other gases. Its small specific surface area and poor CO2 adsorption effect make it difficult to meet the application requirements of large-scale carbon capture technology. Organic amine impregnation is a modification method to improve the CO2 selectivity and adsorption capacity of carbon materials, but it requires carbon materials with a large specific surface area and a porous structure, which existing honeycomb activated carbon cannot meet. Summary of the Invention

[0004] The purpose of this disclosure is to provide an amine-modified honeycomb adsorption module and its preparation method. The preparation method is simple, generates no waste liquid, significantly improves CO2 adsorption capacity, and is suitable for large-scale production and application.

[0005] The first aspect of this disclosure provides a method for preparing an amine-modified honeycomb adsorption module, the method comprising:

[0006] (1) Mix low-ash coal and coal tar pitch, and pre-oxidize, carbonize and first activate the resulting mixture to obtain activated carbon material;

[0007] (2) The activated carbon material, binder, water and optional auxiliary agent are mixed, and the resulting mixed mud is vacuum kneaded, shaped and second activated to obtain a honeycomb adsorption module;

[0008] (3) The honeycomb adsorption module is immersed in a solution containing organic amine, and the resulting material is dried;

[0009] Wherein, based on the total weight of the mixture, the ash content in the mixture is less than 5% by weight.

[0010] Optionally, in step (1), the specific surface area of ​​the activated carbon material is 2000–2700 m². 2 / g.

[0011] Optionally, in step (2), the specific surface area of ​​the honeycomb adsorption module is 1400–2400 m². 2 / g, pore size 1.5–3.5 nm, pore volume 1–2 cm³ 3 / g.

[0012] Optionally, in step (1), the weight ratio of the low-ash coal and coal tar pitch is 1:(0.03-3), preferably 1:(0.05-2); the pre-oxidation conditions include: being carried out in an oxygen-containing atmosphere at a temperature of 200-400℃ for 1-3 hours; the carbonization conditions include: being carried out in an inert gas atmosphere at a temperature of 450-650℃ for 1-3 hours; the inert gas includes one or more of nitrogen, argon, helium, neon, krypton, and xenon; the first activation conditions include: being carried out in a water vapor atmosphere at a temperature of 700-900℃ for 1-2 hours.

[0013] Optionally, in step (2), the binder includes one or more of porous clay, methylcellulose, coal tar, polyacryl alcohol, carboxymethyl cellulose, and wood tar; the auxiliary agent includes one or more of phenolic resin, 4A molecular sieve, 13X molecular sieve, and 5A molecular sieve; based on the dry weight of the mixed mud, the content of activated carbon material is 70-90% by weight, the content of binder is 10-30% by weight, and the content of auxiliary agent is 0-10% by weight.

[0014] Optionally, in step (2), the conditions for vacuum slurry preparation include: a vacuum degree of 80-100 kPa, a temperature of 20-40°C, and a time of 2-6 h; the conditions for molding include: extrusion molding using a honeycomb ceramic extruder, a working temperature of 20-40°C, and an extrusion pressure of 200-300 kN; the conditions for the second activation include: being carried out in a nitrogen atmosphere, a temperature of 300-700°C, and a time of 1-3 h.

[0015] Optionally, in step (3), the immersion conditions include: under ultrasonic conditions, completely immersing the honeycomb adsorption module in a solution containing organic amine; the weight ratio of the organic amine to the honeycomb adsorption module is (0.1-1):1, the ultrasonic frequency is 30-40KHz, the temperature is 20-80℃, and the time is 1-4h.

[0016] Optionally, the organic amine has a molecular weight of 100 to 600. Preferably, the organic amine is selected from one or more of 3-aminopropyltriethoxysilane, polyethyleneimine, diethylenetriamine, tetraethylenepentamine, and pentaethylenehexamine; the solution is selected from ethanol or water.

[0017] Optionally, the method further includes, prior to the mixing in step (1), pulverizing the low-ash coal and coal tar pitch separately to a particle size of less than 150 μm; based on the total weight of the low-ash coal, the fixed carbon content in the low-ash coal is 50-60% by weight, the ash content is less than 5% by weight, and the volatile matter content is 35-45% by weight; based on the total weight of the coal tar pitch, the fixed carbon content in the coal tar pitch is 40-50% by weight, the ash content is less than 1% by weight, and the volatile matter content is 50-60% by weight.

[0018] The second aspect of this disclosure provides an amine-modified honeycomb adsorption module prepared by the preparation method described in the first aspect of this disclosure. The amine-modified honeycomb adsorption module is cylindrical, cuboid, or cube in shape. Multiple openings are distributed on part or all of the main surface of the amine-modified honeycomb adsorption module. The cross-sectional shape of the openings is one or more of the following: circular, square, rectangular, rhomboid, triangular, hexagonal, and elliptical.

[0019] The preparation method provided in this disclosure uses low-ash coal and coal tar pitch as raw materials, followed by pre-oxidation, carbonization, and first activation to obtain activated carbon materials with high specific surface area. Then, by adding a binder, a honeycomb adsorption module with high specific surface area and suitable pore structure is prepared. Impregnation with organic amines yields a novel amine-modified honeycomb adsorption module, which significantly improves CO2 adsorption capacity. The preparation method of this disclosure is simple, generates no waste liquid, and is suitable for large-scale production and application.

[0020] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Detailed Implementation

[0021] The following provides a detailed description of specific embodiments of this disclosure. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit this disclosure.

[0022] The first aspect of this disclosure provides a method for preparing an amine-modified honeycomb adsorption module, the method comprising:

[0023] (1) Mix low-ash coal and coal tar pitch, and pre-oxidize, carbonize and first activate the resulting mixture to obtain activated carbon material;

[0024] (2) The activated carbon material, binder, water and optional auxiliary agent are mixed, and the resulting mixed mud is vacuum kneaded, shaped and second activated to obtain a honeycomb adsorption module;

[0025] (3) The honeycomb adsorption module is immersed in a solution containing organic amine, and the resulting material is dried;

[0026] Wherein, based on the total weight of the mixture, the ash content in the mixture is less than 5% by weight, preferably 0.1 to 3% by weight, more preferably 0.1 to 2.5% by weight.

[0027] The preparation method disclosed herein uses low-ash coal and coal tar pitch as raw materials, followed by pre-oxidation, carbonization, and primary activation to obtain activated carbon material with a high specific surface area. A honeycomb adsorption module with a high specific surface area and suitable pore structure is then prepared by adding a binder. Impregnation with an organic amine yields a novel amine-modified honeycomb adsorption module, which exhibits significantly improved CO2 adsorption capacity. This preparation method is simple, generates no waste liquid, and is suitable for large-scale production and application.

[0028] In one embodiment of this disclosure, in step (1), the specific surface area of ​​the activated carbon material is 2000–2700 m². 2 / g, preferably 2100~2500m 2 / g. In the above embodiments, by selecting preferred activated carbon materials, a honeycomb adsorption module with a high specific surface area can be obtained, which is beneficial to improving the effect of organic amine impregnation.

[0029] In one embodiment of this disclosure, in step (2), the specific surface area of ​​the honeycomb adsorption module is 1400–2400 m². 2 / g, preferably 1500-2000m 2 / g; pore size is 1.5–3.5 nm, preferably 2–3 nm; pore volume is 1–2 cm³. 3 / g, preferably 1.5~2cm 3 / g. In the above embodiments, by selecting a honeycomb adsorption module with preferred specific surface area, pore size and pore volume, it is beneficial for organic amines to be loaded on the pore structure of the honeycomb adsorption module, thereby improving the amine modification effect and thus improving the selectivity and adsorption capacity for CO2.

[0030] In one embodiment of this disclosure, the method further includes, prior to the mixing in step (1), pulverizing the low-ash coal and coal tar pitch separately to a particle size of less than 150 μm, preferably 50–100 μm; based on the total weight of the low-ash coal, the fixed carbon content in the low-ash coal is 50–60% by weight, and the ash content is less than 5% by weight, preferably 0–5% by weight, more preferably 0.1–3% by weight, for example, the ash content in the low-ash coal can be 0.1% by weight, 1.5% by weight, 3% by weight, or 4.5% by weight; the volatile matter content is 35–45% by weight; based on the total weight of the coal tar pitch, the fixed carbon content in the coal tar pitch is 40–50% by weight, and the ash content is less than 1% by weight, preferably 0–1% by weight, more preferably 0.1–0.7% by weight, for example, the ash content in the coal tar pitch can be 0.1% by weight, 0.5% by weight, or 0.8% by weight; the volatile matter content is 50–60% by weight. In the above embodiments, by selecting the preferred pulverization process, the specific surface area of ​​low-ash coal and coal tar pitch can be increased, which is conducive to the full contact between low-ash coal and coal tar pitch and increases the reaction sites; by selecting the preferred low-ash coal and coal tar pitch as raw materials, there is no need to use strong acid for impurity removal, no waste liquid is generated, and it is environmentally friendly.

[0031] In one embodiment of this disclosure, in step (1), the weight ratio of the low-ash coal and coal tar pitch is 1:(0.03-3), preferably 1:(0.05-2); the pre-oxidation conditions include: being carried out in an oxygen-containing atmosphere at a temperature of 200-400°C for 1-3 hours; in a specific embodiment, the pre-oxidation is carried out in an air or oxygen atmosphere; the carbonization conditions include: being carried out in an inert gas atmosphere at a temperature of 450-650°C for 1-3 hours; the inert gas includes one or more of nitrogen, argon, helium, neon, krypton, and xenon; the first activation conditions include: being carried out in a water vapor atmosphere at a temperature of 700-900°C for 1-2 hours. In the above embodiments, by selecting the preferred low-temperature pre-oxidation treatment, small molecules in the mixture can be cross-linked through oxidation to form a macromolecular network structure, thereby improving the yield and adsorption performance of the activated carbon material; by selecting the preferred high-temperature carbonization treatment, volatile components and moisture in the mixture can be removed, thereby improving the strength of the carbonized material and enabling the carbonized particles to form preliminary pores; by selecting the preferred steam first activation treatment, pores can be further formed and expanded on the basis of the carbonized material.

[0032] In one embodiment of this disclosure, in step (2), the binder includes one or more of porous clay, methylcellulose, coal tar, polyacryl alcohol, carboxymethyl cellulose, and wood tar; the auxiliary agent includes one or more of phenolic resin, 4A molecular sieve, 13X molecular sieve, and 5A molecular sieve; based on the dry weight of the mixed mud, the content of the activated carbon material is 70-90% by weight, preferably 75-80% by weight; the content of the binder is 10-30% by weight, preferably 15-20% by weight; and the content of the auxiliary agent is 0-10% by weight, preferably 0-8% by weight. In the above embodiment, by selecting preferred binders and auxiliary agents, the plasticity and component uniformity of the mixed mud can be improved, the strength of the module can be increased, and the CO2 adsorption capacity of the module can be increased.

[0033] In one embodiment of this disclosure, the conditions for vacuum slurry preparation in step (2) include: a vacuum degree of 80–100 kPa, a temperature of 20–40°C, and a time of 2–6 h; the conditions for molding include: extrusion molding using a honeycomb ceramic extruder, a working temperature of 20–40°C, and an extrusion pressure of 200–300 kN; the conditions for the second activation include: being carried out under a nitrogen atmosphere, a temperature of 300–700°C, and a time of 1–3 h. In the above embodiment, selecting the preferred vacuum slurry preparation conditions can make the component distribution in the mixed slurry more uniform and reduce module cracking; selecting the preferred molding treatment can increase the strength of the mixed slurry; selecting the preferred second activation can further increase the water resistance and adsorption performance of the honeycomb adsorption module.

[0034] In one embodiment of this disclosure, step (3) includes the following impregnation conditions: under ultrasonic conditions, the honeycomb adsorption module is completely impregnated in a solution containing an organic amine; the weight ratio of the organic amine to the honeycomb adsorption module is (0.1-1):1; the ultrasonic frequency is 30-40 kHz; the temperature is 20-80°C; and the time is 1-4 h. In the above embodiment, by selecting preferred impregnation conditions, organic amine molecules can be more easily dispersed and impregnated into the pores of the honeycomb adsorption module, thereby improving the adsorption capacity of the honeycomb adsorption module for CO2.

[0035] In one embodiment of this disclosure, the organic amine has a molecular weight of 100-600. Preferably, the organic amine is selected from one or more of 3-aminopropyltriethoxysilane, polyethyleneimine, diethylenetriamine, tetraethylenepentamine, and pentaethylenehexamine; the solution can be ethanol or water. In the above embodiments, by selecting preferred organic amines, the effect of amine modification of the honeycomb adsorption module can be further improved.

[0036] The second aspect of this disclosure provides an amine-modified honeycomb adsorption module prepared by the method described in the first aspect of this disclosure. The amine-modified honeycomb adsorption module is cylindrical, cuboid, or cubic in shape. Multiple openings are distributed on part or all of the main surface of the amine-modified honeycomb adsorption module. The cross-sectional shape of the openings is one or more of the following: circular, square, rectangular, rhomboid, triangular, hexagonal, and elliptical. The cross-sectional shape of the opening refers to the shape of its cross-section, i.e., the shape of the opening is determined by a plane parallel to the plane containing the opening. In the above embodiments, the cross-sectional shape of the openings in the amine-modified honeycomb adsorption module is not limited and can be polygonal or irregular. In a preferred embodiment, the cross-sectional shape of the openings is circular, square, rectangular, rhomboid, triangular, hexagonal, or elliptical.

[0037] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited thereto.

[0038] Unless otherwise specified, all raw materials used in the following examples and comparative examples are commercially available products.

[0039] Example 1

[0040] (1) Xinjiang coal (low ash coal) and coal tar pitch were crushed separately to a particle size of 100 mesh. The crushed Xinjiang coal and coal tar pitch were then mixed evenly (the weight ratio of Xinjiang coal to coal tar pitch was 1:0.15) to obtain a mixture. Based on the total weight of the mixture, the ash content in the mixture was 1.98% by weight. The mixture was placed in a muffle furnace for pre-oxidation in air atmosphere at a temperature of 300℃ for 1 hour. The pre-oxidized sample was then carbonized in a tube furnace under nitrogen atmosphere at a temperature of 600℃ for 1 hour. After carbonization, the sample was first activated in a tube furnace under steam atmosphere at a temperature of 900℃ for 1 hour. After cooling, a specific surface area of ​​2475 m² was obtained. 2 / g of activated carbon material; based on the total weight of Xinjiang coal, the fixed carbon content in Xinjiang coal is 54.45% by weight, the ash content is 2.25% by weight, and the volatile matter content is 37.99% by weight; based on the total weight of coal tar pitch, the fixed carbon content in coal tar pitch is 45.73% by weight, the ash content in coal tar pitch is 0.19% by weight, and the volatile matter content in coal tar pitch is 53.83% by weight;

[0041] (2) Activated carbon material, methylcellulose, and water were mixed in a weight ratio of 0.8:0.2:1 to form a plastic mixed slurry. The slurry was then vacuum-kneaded under a vacuum of 100 kPa, a temperature of 30°C, and a time of 4 hours. The resulting product was extruded using a honeycomb ceramic extruder (working temperature 20–40°C, extrusion pressure 300 kN). A second activation treatment was then performed under a nitrogen atmosphere (temperature 500°C, time 2 hours) to obtain a specific surface area of ​​1980 m². 2 / g of honeycomb adsorption module;

[0042] (3) Under ultrasonic conditions, the honeycomb adsorption module is completely immersed in a mixed solution of diethylenetriamine and ethanol, wherein the weight ratio of diethylenetriamine to honeycomb adsorption module is 0.5:1; the ultrasonic frequency is 40KHz, the temperature is 80℃, and the time is 180min; the immersed honeycomb adsorption module is dried in an oven to obtain amine-modified honeycomb adsorption module 1; its shape is a cube, and multiple openings are distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0043] Example 2

[0044] Similar to Example 1, the only difference is that in step (1), the weight ratio of Xinjiang coal to coal tar pitch is 1:0.05, the ash content in the mixture is 2.15% by weight, the pre-oxidation temperature is 350℃ and the time is 1h; the carbonization temperature is 500℃ and the time is 1h; the first activation temperature is 800℃ and the time is 1h, resulting in a specific surface area of ​​2113 m². 2 / g of activated carbon material;

[0045] In step (2), activated carbon material, porous clay, 4A molecular sieve, and water are mixed in a weight ratio of 0.75:0.15:0.1:1 to form a plastic mixed mud. After vacuum kneading, molding, and a second activation treatment, a specific surface area of ​​1585 m² is obtained. 2 / g of honeycomb adsorption module;

[0046] In step (3), under ultrasonic conditions, the honeycomb adsorption module is completely immersed in a mixed solution of polyethyleneimine, 3-aminopropyltriethoxysilane and ethanol, wherein the weight ratio of polyethyleneimine, 3-aminopropyltriethoxysilane and honeycomb adsorption module is 0.3:0.3:1; the immersed honeycomb adsorption module is dried in an oven to obtain amine-modified honeycomb adsorption module 2; its shape is cuboid, and multiple openings are distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0047] Example 3

[0048] Similar to Example 1, the only difference is that in step (1), the weight ratio of Xinjiang coal to coal tar pitch is 1:1, the ash content in the mixture is 1.22% by weight, the pre-oxidation temperature is 200℃, and the time is 1h; the carbonization temperature is 550℃, and the time is 1h; the first activation temperature is 850℃, and the time is 1h, resulting in a specific surface area of ​​2350m². 2 / g of activated carbon material;

[0049] In step (2), activated carbon material, methylcellulose, phenolic resin and water are mixed in a weight ratio of 0.7:0.2:0.1:1 to form a plastic mud. After vacuum kneading, molding and second activation treatment, a specific surface area of ​​1645 m² is obtained. 2 / g of honeycomb adsorption module;

[0050] In step (3), under ultrasonic conditions, the honeycomb adsorption module is completely immersed in a mixed solution of tetraethylenepentamine and ethanol, wherein the weight ratio of tetraethylenepentamine to the honeycomb adsorption module is 1:1; the immersed honeycomb adsorption module is dried in an oven to obtain amine-modified honeycomb adsorption module 3; its shape is a cube, and multiple openings are distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0051] Example 4

[0052] Similar to Example 1, except that the weight ratio of Xinjiang coal to coal tar pitch was 1:0.01, resulting in an ash content of 2.23% by weight and a specific surface area of ​​1799 m². 2 / g of activated carbon material and a specific surface area of ​​1439m² 2 / g of the honeycomb adsorption module, thereby obtaining the amine-modified honeycomb adsorption module 4; its shape is a cube, and multiple openings are distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0053] Example 5

[0054] Similar to Example 2, except that activated carbon material, porous clay, 4A molecular sieve, and water were mixed in a weight ratio of 0.6:0.3:0.1:1 to form a plastic mixed slurry, resulting in a specific surface area of ​​1485 m². 2 / g of the honeycomb adsorption module, thus obtaining the amine-modified honeycomb adsorption module 5; its shape is a cube, and multiple openings are distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0055] Example 6

[0056] Similar to Example 1, except that the weight ratio of diethylenetriamine to the honeycomb adsorption module is 2:1, resulting in an amine-modified honeycomb adsorption module 6; its shape is cuboid, with multiple openings distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0057] Example 7

[0058] Similar to Example 1, except that the weight ratio of diethylenetriamine to the honeycomb adsorption module is 0.01:1, resulting in an amine-modified honeycomb adsorption module 7; its shape is a cube, with multiple openings distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0059] Comparative Example 1

[0060] Similar to Example 1, except that Xinjiang coal and coal tar pitch are replaced with the same weight of lignite. Based on the total weight of lignite, the lignite contains 45% fixed carbon, 19% ash, and 36% volatile matter, resulting in the comparative honeycomb adsorption module 1. The module is cube-shaped, with multiple openings distributed on part or all of the main surface. The cross-sectional shape of the openings is circular.

[0061] Comparative Example 2

[0062] Similar to Example 1, except that coal tar pitch is replaced with the same weight of Xinjiang coal, and the ash content in the mixture is 2.25% by weight, resulting in the comparative honeycomb adsorption module 2; its shape is a cube, and multiple openings are distributed on part or all of the main surface, with the cross-sectional shape of the openings being circular.

[0063] Comparative Example 3

[0064] Similar to Example 1, except that Xinjiang coal is replaced with the same weight of coal tar pitch, and the ash content in the mixture is 0.19% by weight, resulting in the comparative honeycomb adsorption module 3; its shape is a cube, and multiple openings are distributed on part or all of the main surface, with the cross-sectional shape of the openings being circular.

[0065] Comparative Example 4

[0066] Similar to Example 1, except that, under ultrasonic conditions, a honeycomb adsorption module (coal-based material, commercially available) with an iodine value of 800 was completely immersed in a mixed solution of polyethyleneimine and ethanol, wherein the weight ratio of polyethyleneimine to the honeycomb adsorption module was 0.5:1, resulting in a comparative honeycomb adsorption module 4; its shape is a cube, and multiple openings are distributed on part or all of the main surface, with the cross-sectional shape of the openings being circular.

[0067] Comparative Example 5

[0068] Similar to Example 1, except that, under ultrasonic conditions, a honeycomb adsorption module (coal-based material, commercially available) with an iodine value of 800 was completely immersed in a mixed solution of polyethyleneimine and ethanol, wherein the weight ratio of polyethyleneimine to the honeycomb adsorption module was 0.2:1, resulting in a comparative honeycomb adsorption module 5; its shape is a cube, and multiple openings are distributed on part or all of the main surface, with the cross-sectional shape of the openings being circular.

[0069] Comparative Example 6

[0070] Similar to Example 1, the only difference is that the honeycomb adsorption module obtained in step (2) is dried in an oven to obtain the comparative honeycomb adsorption module 6; its shape is a cube, and multiple openings are distributed on part or all of the main surface, and the cross-sectional shape of the openings is circular.

[0071] Test case

[0072] (1) The specific surface area, pore size and pore volume of the activated carbon materials prepared in the test examples and comparative examples (before impregnation with organic amines) are shown in Table 1.

[0073] (2) The CO2 adsorption capacity of the amine-modified honeycomb adsorption modules prepared in Examples 1-7 and the comparative honeycomb adsorption modules prepared in Comparative Examples 1-6 was tested. The test method was as follows: CO2 adsorption was carried out in a fixed-bed reactor. Before the reaction, the adsorption module was pretreated under nitrogen and 150°C. Then, a CO2 / N2 mixed gas was introduced for adsorption. The adsorption conditions were: under a simulated flue gas atmosphere (CO2 volume content of 15%, N2 volume content of 85%), temperature of 40°C, adsorption for 0.5 h, and CO2 adsorption capacity = (weight of CO2 adsorbed by the amine-modified honeycomb adsorption module / weight of the amine-modified honeycomb adsorption module) × 100%. The results are shown in Table 1.

[0074] Table 1

[0075]

[0076] The data above shows that the amine-modified honeycomb adsorption modules obtained using the method of this disclosure in Examples 1-7 have high CO2 adsorption capacity. Specifically, a comparison of the data from Examples 1 and 4 shows that when Example 1 uses the preferred embodiment of this disclosure, where the weight ratio of low-ash coal and coal tar pitch is 1:(0.03-3), a honeycomb adsorption module with a large specific surface area and suitable pore structure can be obtained. This is beneficial for loading organic amines onto the pore structure, improving the amine modification effect, and thus increasing the CO2 adsorption capacity. A comparison of the data from Examples 1 and 5 shows that Example 1 uses the preferred embodiment of this disclosure, where the content of activated carbon material is 70-90% by weight, the content of binder is 10-30% by weight, and the content of auxiliary agent is 0-1% by weight. In the 0% by weight implementation, the component distribution of the mixed mud is more uniform, and the CO2 adsorption capacity is higher. A comparison of the data from Examples 1 and 6 shows that in Example 1, when the preferred organic amine to honeycomb adsorption module weight ratio of this disclosure is (0.1-1), the organic amine is less likely to clog the pores of the honeycomb adsorption module, resulting in a higher CO2 adsorption capacity. A comparison of the data from Examples 1 and 7 shows that in Example 1, when the preferred organic amine to honeycomb adsorption module weight ratio of this disclosure is (0.1-1), the organic amine can be better loaded onto the honeycomb adsorption module, achieving a modification effect and thus increasing the CO2 adsorption capacity. Comparative Examples 1-6 did not use the method of this disclosure, and the CO2 adsorption capacity of the comparative honeycomb adsorption modules obtained was lower. Therefore, the methods provided in Examples 1-7 of this disclosure are superior to those in Comparative Examples 1-6.

[0077] The preferred embodiments of this disclosure have been described in detail above. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0078] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0079] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A method for preparing an amine-modified honeycomb adsorption module, characterized in that, The preparation method includes: (1) Mix low-ash coal and coal tar pitch, and pre-oxidize, carbonize and first activate the resulting mixture to obtain activated carbon material; (2) The activated carbon material, binder, water and optional auxiliary agent are mixed, and the resulting mixed mud is vacuum kneaded, shaped and second activated to obtain a honeycomb adsorption module; (3) The honeycomb adsorption module is immersed in a solution containing organic amine, and the resulting material is dried; The low-ash coal is Xinjiang coal with an ash content of less than 2.25% by weight, and the ash content in the mixture is less than 5% by weight, based on the total weight of the mixture.

2. The preparation method according to claim 1, characterized in that, In step (1), the specific surface area of ​​the activated carbon material is 2000~2700 m². 2 / g.

3. The preparation method according to claim 1, characterized in that, In step (2), the specific surface area of ​​the honeycomb adsorption module is 1400~2400m². 2 / g, pore size 1.5~3.5nm, pore volume 1~2cm 3 / g.

4. The preparation method according to claim 1, characterized in that, In step (1), the weight ratio of the low-ash coal and coal tar pitch mixture is 1:(0.03~3). The pre-oxidation conditions include: being carried out in an oxygen-containing atmosphere at a temperature of 200~400℃ for 1~3 hours; The carbonization conditions include: being carried out in a nitrogen or inert gas atmosphere at a temperature of 450~650℃ for 1~3 hours; the inert gas includes one or more of argon, helium, neon, krypton and xenon. The conditions for the first activation include: being carried out in a water vapor atmosphere at a temperature of 700~900℃ for 1~2 hours.

5. The preparation method according to claim 4, characterized in that, In step (1), the weight ratio of the low-ash coal and coal tar pitch is 1:(0.05~2).

6. The preparation method according to claim 1, characterized in that, In step (2), the binder includes one or more of porous clay, methylcellulose, coal tar, polyacryl alcohol, carboxymethyl cellulose and wood tar; the auxiliary agent includes one or more of phenolic resin, 4A molecular sieve, 13X molecular sieve and 5A molecular sieve. Based on the dry weight of the mixed mud, the content of the activated carbon material is 70-90% by weight, the content of the binder is 10-30% by weight, and the content of the auxiliary agent is 0-10% by weight.

7. The preparation method according to claim 1, characterized in that, In step (2), the conditions for vacuum plowing include: vacuum degree of 80~100KPa, temperature of 20~40℃, and time of 2~6h; The molding conditions include: extrusion molding using a honeycomb ceramic extruder, with a working temperature of 20~40℃ and an extrusion pressure of 200~300kN; The conditions for the second activation include: being carried out under a nitrogen atmosphere at a temperature of 300~700℃ for 1~3 hours.

8. The preparation method according to claim 1, characterized in that, In step (3), the immersion conditions include: under ultrasonic conditions, the honeycomb adsorption module is completely immersed in a solution containing organic amine; the weight ratio of the organic amine to the honeycomb adsorption module is (0.1~1):1, the ultrasonic frequency is 30~40KHz, the temperature is 20~80℃, and the time is 1~4h.

9. The preparation method according to claim 1, characterized in that, The organic amine has a molecular weight of 100-600, and the solution is selected from ethanol or water.

10. The preparation method according to claim 9, characterized in that, The organic amine is selected from one or more of 3-aminopropyltriethoxysilane, polyethyleneimine, diethylenetriamine, tetraethylenepentamine, and pentaethylenehexamine.

11. The preparation method according to claim 1, characterized in that, The method further includes, prior to the mixing in step (1), pulverizing the low-ash coal and coal tar pitch separately to a particle size of less than 150 μm; Based on the total weight of the low-ash coal, the fixed carbon content in the low-ash coal is 50-60% by weight, and the volatile matter content is 35-45% by weight; based on the total weight of the coal tar pitch, the fixed carbon content in the coal tar pitch is 40-50% by weight, the ash content is less than 1% by weight, and the volatile matter content is 50-60% by weight.

12. An amine-modified honeycomb adsorption module prepared by the preparation method according to any one of claims 1 to 11, characterized in that, The amine-modified honeycomb adsorption module is cylindrical, cuboid, or cube-shaped. Multiple openings are distributed on part or all of the main surface of the amine-modified honeycomb adsorption module. The cross-sectional shape of the openings is one or more of the following: circular, rectangular, rhomboid, triangular, hexagonal, and elliptical.

Citation Information

Patent Citations

  • Preparation method of flue gas denitrification catalyst with honeycomb activated carbon as carrier

    CN102441373A

  • Photocatalytic cellular activated carbon net

    CN104549370A